Improving Student Learning Outcomes Using the Mind Mapping Method - Mutaqin, Asep Sofyan; Nurhamzah (Department of Teacher Professional Education, Tarbiya and Teacher Training Faculty, UIN Sunan Gunung Djati Bandung, 2024)
A preliminary study at SDN 224 Cijambe found two key issues: students' limited understanding of Islamic Religious Education and low learning outcomes on Asmaul Husna in grade V. This study aims to: 1) examine the learning process with Mind Mapping, 2) assess learning outcomes after using this method, and 3) determine if Mind Mapping can improve student performance in PAI on Asmaul Husna material. The research, a classroom action study (PTK), used Elliot's Spiral model across two cycles, each involving planning, action, observation, and reflection stages. Conducted in grade V with 28 students, data collection utilized observation, tests, and documentation. Results showed that only 5 students (17.86%) met objectives in the pre-cycle, increasing to 8 students (28.57%) in the first cycle and reaching 20 students (71.43%) in the second cycle. Thus, Mind Mapping was found to significantly enhance learning outcomes, supporting student comprehension and engagement in PAI at SDN 224 Cijambe, Bandung.